2019
DOI: 10.32911/as.2018.v11.n2.577
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de hatos ganaderos en la cuenca baja del río Shanusi Alto Amazonas – Loreto – Perú

Abstract: <p>El objetivo fue la caracterización de los hatos ganaderos productores de leche de la cuenca baja del rio Shanusi Alto Amazonas – Loreto-Perú. En la metodología se aplicó encuestas a 26 ganaderos, se usó la estadística descriptiva, para la tipificación se aplicó el análisis de conglomerado de K-medias. Las variables cuantitativas: producción de leche 6,33 litros/vaca, el precio S/ 0,86/litro teniendo en producción 5 vacas/hato, promedio de 14 has con pasturas mejoradas, la carga animal de 1,8 UA/ha, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In this study, 97.1% of livestock farmers reported that they practice at least one additional economic activity, that is, a diversified income source, thus the indicator "diversification of income from the farm" was the one with the highest value. In the same line, Mathios, Alegre, and Aguilar (2018) reported that livestock farmers from the lower Shanushi River basin in Yurimaguas practice additional agricultural activities with some working in commerce and in the public sector, which shows a diversification in their income sources. The diversification of income by rural households has the potential to spread economic risk, smooth consumption, and enhance the efficiency of use of natural resources (Caviglia-Harris & Sills, 2005).…”
Section: Economic Sustainabilitymentioning
confidence: 90%
“…In this study, 97.1% of livestock farmers reported that they practice at least one additional economic activity, that is, a diversified income source, thus the indicator "diversification of income from the farm" was the one with the highest value. In the same line, Mathios, Alegre, and Aguilar (2018) reported that livestock farmers from the lower Shanushi River basin in Yurimaguas practice additional agricultural activities with some working in commerce and in the public sector, which shows a diversification in their income sources. The diversification of income by rural households has the potential to spread economic risk, smooth consumption, and enhance the efficiency of use of natural resources (Caviglia-Harris & Sills, 2005).…”
Section: Economic Sustainabilitymentioning
confidence: 90%
“…Concerning this, the importance of developing associative practices has been highlighted. Thus, knowledge dissemination processes can be generated among farmers, from social interaction among peers in the territories, as evidenced in the studies of Tu et al (2018), Mathios Flores et al (2019), Li et al (2021), andYue et al (2023). Participation in training in the cultivation of arracacha, with learning-by-doing methodologies such as the new field school approaches generates processes of dialogue of knowledge and knowledge for the adoption of practices and innovations (Khumairoh et al, 2019;Navarro-Niño et al, 2022).…”
Section: Arracacha Farmers With High Levels Of Adoption Of Innovation...mentioning
confidence: 99%